Correlation of odontogenic infection severity score with C-reactive protein levels on patients with odontogenic infection in Dr Hasan Sadikin General Hospital Bandung - Prihandana, Ariyaka Niastya; Yusuf, Harmas Yazid; Nurwiadh, Agus; Lismayanti, Leni (Padjadjaran Journal of Dentistry, 2021)
Introduction:  Head and neck infections commonly caused by spreading odontogenic infection, which able to cause a local and systemic manifestation, from mild to severe complications according to its severity. Assessment of the severity of odontogenic infections is essential to determine the prognosis, assessed through local and systemic parameters. Laboratory examination used to examine the biological marker that indicates the ongoing infection. C-reactive protein (CRP) is a protein synthesised by hepatocytes in response to the body's inflammatory process, including odontogenic infection. This study was aimed to analyse the severity score of odontogenic infections using the CRP levels in patients with odontogenic infections. Methods: An analytic study with a cross-sectional approach was conducted on 30 patients of Dr Hasan Sadikin General Hospital Bandung diagnosed with odontogenic infections, determined by calculations according to Hosmer and Lemeshow. Assessment of the severity score in odontogenic infections and quantitative CRP levels with the Dimension tool was conducted afterwards. Correlation between odontogenic infection severity score and CRP levels was analysed using regression and correlation tests. Results: From 30 subjects, there was found 33.3% with mild severity score, 63.3% moderate score and 3.3% severe score. The mean of the CRP level was significantly increased according to the odontogenic severity scoring category. All research subjects who were examined showed that there was a very strong and significant correlation (p-value<0.05) between the severity of odontogenic infections and CRP levels in odontogenic infection patients with a correlation coefficient r=0.84 (p=0.001). Conclusion: There is a positive correlation between the CRP levels and the severity score of odontogenic infection. The higher the CRP levels, the odontogenic infection will be more severe. Therefore, the CRP level might be considered an additional biomarker in supporting the severity of odontogenic infection in clinical practice.